Nestin Expressed by Pre‐Existing Cardiomyocytes Recapitulated in Part an Embryonic Phenotype; Suppressive Role of p38 MAPK. Issue 7 (27th July 2016) - Meus, Marc‐Andre; Hertig, Vanessa; Villeneuve, Louis; Jasmin, Jean‐Francois; Calderone, Angelino
Abstract : Nestin (+) ‐cardiomyocytes were identified in the ischemically damaged human/rodent heart, albeit the cellular source, and signaling events implicated in the appearance of the intermediate filament protein remained undefined. Expression of the enhanced green fluorescent protein (EGFP) driven by the second intron of the nestin gene identified a subpopulation of EGFP/nestin (+) cells that differentiated to a vascular phenotype in the peri‐infarct/infarct region of post‐MI mice albeit the transgene was not detected in nestin (+) ‐cardiomyocytes. α‐MHC‐driven expression of the reporter mCherry was detected in troponin‐T (+) ‐ and nestin (+) ‐cardiomyocytes in the peri‐infarct/infarct region of post‐MI mice. However, the cell cycle re‐entry of nestin/mCherry (+) ‐cardiomyocytes was not observed. Nestin staining was identified in a paucity of neonatal rat ventricular cardiomyocytes (NNVM). Exposure to phorbol 12, 13‐dibutyrate (PDBu) induced NNVM hypertrophy but did not promote nestin expression or Brdu incorporation. PDBu treatment of NNVMs phosphorylated p38 MAPK and HSP27 and HSP27 phosphorylation was abrogated by the p38 MAPK inhibitor SB203580. PDBu/SB203580 co‐treatment significantly increased the percentage of NNVMs that expressed nestin and incorporated Brdu. In the heart of embryonic 10.5 day mice, nestin immunoreactivity was observed in cycling troponin‐T (+) ‐cardiomyocytes. Nestin was also detected in embryonic rat ventricular cardiomyocytes and depletion of the intermediate filament protein attenuated cell cycle re‐entry. Thus, nestin expressed by pre‐existing cardiomyocytes following ischemic damage recapitulated in part an embryonic trait and may provide the requisite phenotype to initiate cell cycle re‐entry. However, the overt activation of the p38 MAPK pathway post‐MI may in part limit the appearance and inhibit the cell cycle re‐entry of nestin (+) ‐cardiomyocytes. J. Cell. Physiol. 232: 1717–1727, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Nestin was expressed by pre‐existing cardiomyocytes following ischemic damage to the adult heart and recapitulated in part an embryonic phenotype. However, nestin‐expressing cardiomyocytes were unable to re‐enter the cell cycle following ischemic damage because of the suppressive effect of the p38 MAPK pathway.